Age, parity and birth spacing to the incidence of preeclampsia - Reza Kartikadewi; Endah Marianingsih Theresia; Niken Meilani (Intelektual Pustaka Media Utama, 2019)
Preeklampsia is complication in pregnancy characterized by various symptoms as clinical hypertension and protein urine and usually occurs after the age of 20 weeks of pregnancy until 48 hours after labor. Highest Insidence of preeclampsia in DIY was in Sleman (22%- 30%). Preeclampsia was caused by multy factoral. Goal of this research aimed to know the the correlation between age, parity and birth spacing to the preeclampsia. The research used Cross sectional design with purposive sampling technique. The subject of this research was 381 labor patiens in RSUD Sleman in 2016. The data were collected from register book and medic record of labor in 2016. The data were analyzed using Chi squareand logistic regression. The analysis showed of most subjects aged ≥30 years, had parity 2, had a gestational distance of 2-5, and did not have preeclampsia.As the result showed age ≥30 years had a significant association with preeclampsia p value of 0.023 Exp B 10.630 95% CI: 1.378 to 82.005. Distance pregnancy <2 years had a significant association with preeclampsia p value 0,000 Exp B 3,201 95% CI: 1.862 to 5.503, and the distance Pregnancy >5 years had a p-value 0.013 with Exp B 3,622 95% CI: 1.308 to 10.026.The conclusion of this research shows that there is a relationship between age and the incidence of preeclampsia pregnancy spacing.